Efektivitas Pembelajaran Kontekstual (CTL) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pendidikan Agama Kristen - Karina Onmilka; Tina Tina; Selfina Selfina; Yuwantri Yuwantri; Jessica Putri Manuella; Lelo Lelo; Matius Timan Herdi Ginting (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study looks at how the Contextual Teaching and Learning (CTL) model is used in Christian Religious Education (CRE) and checks how it helps students develop their critical thinking abilities. In today’s education system, students are not just expected to remember Bible stories, but also to understand what they mean, think about the moral lessons, and use Christian values wisely in their everyday lives. However, past observations show that CRE classes often use a lot of lectures and memorization, which doesn’t give students much chance to think deeply or link what they learn to real-life situations. The CTL model provides a better way for learning by using seven key parts: constructivism, inquiry, questioning, learning community, modeling, reflection, and real-world assessmen. A descriptive qualitative design was employed involving CRE teachers and students selected purposively from classes that have integrated CTL in online and face-to-face settings. Data were collected through classroom observations, semi-structured interviews, and instructional documents. The analysis followed Miles and Huberman’s stages of data reduction, display, and conclusion drawing, supported by triangulation to strengthen credibility. The findings reveal that CTL enhances student engagement, promotes higher-order reasoning, and supports the internalization of Christian values in real-life contexts. Supporting factors include a positive school climate, parental involvement, and teacher readiness, whereas obstacles emerge from limited facilities, large class sizes, and insufficient teacher understanding of CTL. The study underscores the need for context-based and character-oriented instructional designs in CRE.